Sox10 cooperates with the mediator subunit 12 during terminal differentiation of myelinating glia - Vogl, Michael; Reiprich, Simone; Küspert, Melanie; Kosian, Thomas; Schrewe, Heinrich; Nave, Klaus-Armin; Wegner, Michael (The Journal of Neuroscience, 2013)
Several transcription factors are essential for terminal differentiation of myelinating glia, among them the high-mobility-group-domain-containing protein Sox10. To better understand how these factors exert their effects and shape glial expression programs, we identified and characterized a physical and functional link between Sox10 and the Med12 subunit of the Mediator complex that serves as a conserved multiprotein interphase between transcription factors and the general transcription machinery. We found that Sox10 bound with two of its conserved domains to the C-terminal region of Med12 and its close relative, Med12-like. In contrast to Med12-like, substantial amounts of Med12 were detected in both Schwann cells and oligodendrocytes. Its conditional glia-specific deletion in mice led to terminal differentiation defects that were highly reminiscent of those obtained after Sox10 deletion. In support of a functional cooperation, both proteins were jointly required for Krox20 induction and were physically associated with the critical regulatory region of the Krox20 gene in myelinating Schwann cells. We conclude that Sox10 functions during terminal differentiation of myelinating glia, at least in part by Med12-dependent recruitment of the Mediator complex.
EVALuna2:4941